AB0678 RISK FACTORS FOR ADVERSE PREGNANCY OUTCOMES IN SPONDYLOARTHRITIS: DISEASE PHENOTYPE AND DISEASE ACTIVITY MAY PLAY A ROLE. (2nd June 2020) - Cruz-Machado, A. R.; Crisafulli, F.; Gerardi, M. C.; Filippini, M.; Fredi, M.; Gorla, R.; Lazzaroni, M. G.; Nalli, C.; Taglietti, M.; Lojacono, A.; Zinardini, C.; Zatti, S.; et al.
Abstract : Background: Pregnant patients (pts) with spondyloarthritis (SpA) seem at increased risk for adverse pregnancy outcomes (APO), however limited and conflicting data have been published so far and risk factors for APO in these pts remain poorly understood. Objectives: To assess APO and identify possible risk factors for those in a cohort of SpA pregnant pts. Methods: Data on SpA pts prospectively-followed in a pregnancy clinic from 2010 to 2019 were retrospectively analysed before conception and during each trimester. Pregnancies complicated by APO were compared with those that were uneventful for demographic and clinical variables. Active disease was defined as a DAS-28-CRP>3.2 or an ASDAS-CRP ≥ 2.1 according to peripheral or axial dominant disease respectively. Results: 56 pregnancies (mean age 34±5 years; median disease duration 60 months, IQR 24-123) in 47 pts were analysed: 37 psoriatic arthritis, 7 axial SpA, 6 undifferentiated SpA, 3 enteropathic SpA, 2 reactive arthritis and 1 enthesitis-related juvenile idiopathic arthritis. APO were recorded in 23/56 (41%) pregnancies: 5 (9%) early miscarriages, 1 (2%) medical abortion (central nervous system malformation), 3 (5%) preterm births (≥34 gestational week, all for preterm premature rupture of membranes - PROM); 2 (4%) PROM; 7 (13%) small for gestational age newborns (SGA); 3 gestational diabetes and 2 cholestasis of pregnancy. Table 1 displays the comparison between pregnancies with and without APO. A higher number of pts with active disease were detected during the 2 nd trimester in both groups, however differences between those were only significant at the 3 rd trimester (p=0.03). History of inflammatory bowel symptoms (IBS) was also associated with an increased risk for APO (p=0.02). Although not reaching statistical significance, APO occurred more frequently in pts with a previous use of > 1 conventional synthetic (cs) or biological (b) disease-modifying antirheumatic drug (DMARD) (p=0.05), suggesting a more difficult to treat phenotype. Likewise, pts with APO were less often treated with low dose aspirin (LDA) during pregnancy. Conclusion: SGA was the main APO recorded. History of IBS, a more difficult to treat phenotype and the presence of active disease during pregnancy influenced APO in this cohort, reinforcing the need for tight disease control before and during pregnancy. Larger and prospective data are warranted to confirm these results and to assess the potential protective role of LDA. References: [1]Molto 2018; Zbinden 2018. Disclosure of Interests: None declared